4π Scatterometer: A new technique for understanding the general and complete scattering properties of particulate media. (May 2020) - Maconi, Göran; Helander, Petteri; Gritsevich, Maria; Salmi, Ari; Penttilä, Antti; Kassamakov, Ivan; Hæggström, Edward; Muinonen, Karri
Highlights: We present the first non-destructive 4π particle scatterometer of its kind. Controlled acoustic levitation allows measuring the sample from any angle. Polarimetric angular maps of light scattering from a mm-sized sample are demonstrated. The non-contact sample manipulation allows handling high-value fragile samples. Abstract: Knowing the optical properties of a sample is important in many scientific fields, such as space science, climate studies, and medicine. In many of these applications, the samples are fragile, unique or available in limited quantities, and have to be subsequently studied by additional techniques, implying that sample preservation is important. Established light scattering single particle measurements involve attaching the sample to a holder or measuring a laminar flow of particles, neither of which allows a controlled, unperturbed non-destructive measurement. Acoustic levitation is a state-of-the-art and non-contacting approach capable of assisting light scattering measurements. However, a full 4π measurement (i.e., a measurement from any direction on the full 4π solid angle) has hither been impossible due to levitation instabilities. Here we present and describe the instrument capable of performing a full 4π light scattering measurement. We measure light scattering properties of millimeter-sized samples at any direction. This is enabled by introducing a novel non-contacting sample holder based on acoustic levitation, which allows a disturbance-free measurement of an orientation-controlled sample. The instrument is scalable and currently employs polarized visible light (400–700 nm). It also measures beam and sample stability as well as temperature and humidity, to ensure consistency of measurements. We demonstrate the 4π capabilities of the instrument by measuring an angular map of light scattering from a polystyrene foam sample, as well as a multi-angular measurement (two semicircular measurements 90° apart) of a sample consisting of agglomerated 500 nm silica spheres. The upper left 2 × 2 submatrix of the Mueller matrix is measured from the sample along the (polar) scattering angle in semi-circular sweeps, changing the azimuthal scattering angle for each sweep. Our results allow for verification of theoretical models by mimicking the conditions of the simulations and by making the measurements directly comparable to model predictions.